Structural, elastic and optical properties of xSrO1OPbO- (90-x)B2O3, xPbO-30SrO-(70x)B2O3 and xSrO-(90-x)B2O3-2CeO28AI2O3 borate glasses in borate anomaly region / Nurul Syahidah Sabri - Sabri, Nurul Syahidah (Institute of Graduate Studies, UiTM, 2018)
Glass samples with the composition of xSrO-10PbO-(90-x)B2O3 (x = 20- 45), xPbO-30SrO-(70-x)B2O3 (x = 0-25) and xSrO-(90-x)B2O3-2CeO2- 8A1203 (x = 25-50 mol%) were prepared by melt-quenching method to elucidate the structural, elastic and optical behavior in borate anomaly region. Characterization techniques like X-ray diffraction (XRD), Fourier transforms infra-red spectroscopy (FTIR), ultrasonic measurement, UV-Visible and Luminescence (for SrO-B203-Ce02-A1203) spectroscopes are employed in the present work. XRD data showed amorphous nature for SrO-PbO-B203 samples while mixed crystalline/amorphous phases for the SrO-B203-Ce02-A1203 samples at x > 35 mol%. FESEM image and EDX analysis revealed that the samples contained Ce-rich crystalline phase and Ce depleted glass phase. FTIR analysis revealed the presence of B04 and B03 vibration groups. Variation of SrO in SrO-PbOB203 and SrO-B203-Ce02-A1203 samples has resulted in increased ultrasonic velocities, elastic moduli (CL, μ, K and Y), hardness (H), Debye temperature (9D) at lower SrO content but decreased for higher SrO addition…